Mies van der Rohe. Progetto per Mansion House Square a Londra - Pireddu, Alberto (Firenze Architettura, 2021)
This article is a critical essay on Mies van der Rohe’s Mansion House Square project in London. The bronze and glass tower and the stone square possess an almost iconic value in that they are a witness of a solid idea of the city, ripened through his experiences in Germany and the United States, which inevitably coincides, having contributed to determine it, with the history of the European city and its evolution during the 20th century.